The Role of Ratio Profits as the Improvement of Realization of KPR BTN Credit in PT. BTN (Persero) Tbk. - Achmad Fauzi (Integrated Journal of Business and Economics (IJBE), 2018)
Mortgages are used as credit services provided by banks to customers who want a special loan to meet the needs in the construction of houses or home renovations that must be in accordance with the procedures that have been specified as a condition of completeness of KPR. Data collection methods in the preparation of this research is a qualitative research method with one case study in calculating the profit generated by Bank BTN (Bank Tabungan Negara) can be calculated by using the ratio. One of the ratios used is the profitability ratio. In the ratio of profitability, there are ratios such as: ROA (Return On Asset), ROE (Return On Equity), NIM (Net Interest Margin), and BOPO (Operational Cost). To find out the ROA (Return On Asset) ratio, net income after tax and income is required. As for calculating ROE (Return On Equity) ratio required net income after interest and taxes and capital. And for NIM (Net Interest Margin) ratio required total net profit after tax and income, while BOPO (Operational Cost) required operational and operational income. Analysis of financial statements is very important to do because at this stage the financial statements that have been calculated on the ratio already described, the ratio results obtained by PT. Bank BTN (Bank Tabungan Negara) may be decided to comply with the provisions of the BI standard provisions.